Podcasts and Vlogs as Educational Tools: Exploring Digital Narratives in Teaching - Baharuddin Baharuddin; Fatima Malik; Ahmed Shah (Yayasan Adra Karima Hubbi, 2026)
Background. The rapid expansion of digital media has transformed educational practices, encouraging the integration of multimedia platforms into teaching and learning processes. Podcasts and vlogs have emerged as accessible and engaging digital narrative formats that enable educators and students to communicate knowledge through audio-visual storytelling. Despite their growing popularity, systematic empirical examination of their effectiveness as pedagogical tools remains limited. Purpose. This study aims to explore the effectiveness of podcasts and vlogs as educational tools in enhancing student engagement and learning outcomes. Method. A mixed-methods research design was employed involving 72 undergraduate students divided into experimental and comparison groups. The experimental group participated in a six-week intervention integrating podcast and vlog production into course activities, while the comparison group received conventional instruction. Data were collected through engagement surveys, academic performance assessments, classroom observations, and semi-structured interviews. Results. Findings indicate that students engaged in podcast and vlog production demonstrated significantly higher levels of cognitive and emotional engagement, along with improved academic performance. Qualitative evidence revealed increased motivation, collaborative interaction, and enhanced communication skills. Conclusion. The study concludes that podcasts and vlogs function as effective digital narrative tools for enriching teaching practices and promoting meaningful learning in contemporary educational contexts.